1999
DOI: 10.1002/(sici)1097-4547(19990115)55:2<187::aid-jnr6>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of glial cell line-derived neurotrophic factor (GDNF) expression in human neuroblastoma and glioblastoma cell lines

Abstract: Human SK-N-AS neuroblastoma and U-87MG glioblastoma cell lines were found to secrete relatively high levels of glial cell line-derived neurotrophic factor (GDNF). In response to growth factors, cytokines, and pharmacophores, the two cell lines differentially regulated GDNF release. A 24-hr exposure to tumor necrosis factor-alpha (TNFalpha; 10 ng/ml) or interleukin-1beta (IL-1,; 10 ng/ml) induced GDNF release in U-87MG cells, but repressed GDNF release from SK-N-AS cells. Fibroblast growth factors (FGF)-1, -2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(18 citation statements)
references
References 66 publications
2
16
0
Order By: Relevance
“…The principal function of IL-10 appears to be limitation and ultimately termination of inflammatory responses (Moore et al, 2001). Therefore, the observation that AS101, which inhibits IL-10 and induces pro-inflammatory molecules, increases GDNF expression is consistent with the findings that pro-inflammatory molecules induce GDNF up-regulation (Appel et al, 1997;Verity et al, 1998Verity et al, , 1999McNaught and Jenner, 2000;Remy et al, 2003;Hashimoto et al, 2005c;Kuno et al, 2006). Also type-2A protein phosphatases (PP) seem to negatively regulate GDNF expression as GDNF levels increase upon their inhibition (Verity et al, 1998).…”
Section: Negative Regulation Of Gdnf Expressionsupporting
confidence: 68%
See 1 more Smart Citation
“…The principal function of IL-10 appears to be limitation and ultimately termination of inflammatory responses (Moore et al, 2001). Therefore, the observation that AS101, which inhibits IL-10 and induces pro-inflammatory molecules, increases GDNF expression is consistent with the findings that pro-inflammatory molecules induce GDNF up-regulation (Appel et al, 1997;Verity et al, 1998Verity et al, , 1999McNaught and Jenner, 2000;Remy et al, 2003;Hashimoto et al, 2005c;Kuno et al, 2006). Also type-2A protein phosphatases (PP) seem to negatively regulate GDNF expression as GDNF levels increase upon their inhibition (Verity et al, 1998).…”
Section: Negative Regulation Of Gdnf Expressionsupporting
confidence: 68%
“…Conflict might arise when comparing the positive impact of IL1b on GDNF levels in glial cell lines (Appel et al, 1997;Verity et al, 1998Verity et al, , 1999, or in mouse astrocyte cell cultures prepared from neonatal cortices (Appel et al, 1997), with the lack of effect of IL-1b on GDNF expression in striatal astrocyte cultures or when injected intrastriatally in mice (Ho and Blum, 1997). In line with this, data from our group indicates that IL-1b is not involved in GDNF upregulation in striatal cultures exposed to conditioned medium from H 2 O 2 -or L-DOPA-challenged substantia nigra neuron-glia cultures (unpublished results), whereas we have shown that IL-1b mediates GDNF up-regulation in substantia nigra cell cultures in response to H 2 O 2 or L-DOPA (Saavedra et al, 2007).…”
Section: Inflammatory Signals and Gdnf Expressionmentioning
confidence: 99%
“…Indeed, elevated GDNF expression is observed in response to LPS and to the pro-inflammatory cytokines IL-1 , IL-6, TNF-and TNF-in C6 cells (Appel et al, 1997;Verity et al, 1998), and in U-87MG glioblastoma cells (Verity et al, 1999). In cultured astrocytes both exogenous TNF-, via TNF receptors, and endogenously produced TNF-induce GDNF expression suggesting that an autocrine loop contributes to the production of neurotrophic factors in response to inflammation (Kuno et al, 2006).…”
Section: Role Of Gdnf In Controlling Microglia Activationmentioning
confidence: 99%
“…In cultured astrocytes both exogenous TNF-, via TNF receptors, and endogenously produced TNF-induce GDNF expression suggesting that an autocrine loop contributes to the production of neurotrophic factors in response to inflammation (Kuno et al, 2006). In contrast, TNF-, TNF-, IL-1 and LPS repress GDNF release in SK-N-AS neuroblastoma cells (Verity et al, 1999). Therefore, it has been proposed that GDNF synthesis and release in response to inflammatory molecules may be differentially regulated in cells of glial and neuronal phenotype (Verity et al, 1999).…”
Section: Role Of Gdnf In Controlling Microglia Activationmentioning
confidence: 99%
See 1 more Smart Citation